Pemeriksaan Kesehatan pada Nelayan di Galesong Takalar, Makassar, Sulawesi Selatan - Irma Fajriah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This community service activity aims to provide health check-ups and awareness programs for fishermen in Galesong Takalar, Makassar, South Sulawesi. Fishermen are vulnerable to various health issues due to prolonged exposure to extreme weather conditions, lack of nutrition, and high physical workload. The program includes general medical check-ups, awareness sessions on occupational health risks, and distribution of basic health kits. The methods used involve community engagement, collaboration with local health centers, and participatory discussions. The results indicate increased health awareness and early detection of common diseases among fishermen, which can improve their quality of life and work productivity.